Using network science to identify the prominent court zone of tennis long rally - Zhou, Y.; Cui, Y.; Cao, R. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: In the process of the tennis match, the interaction between two competing players involves the decision-making of stroke, positioning and ball direction and rotation. To unveil the playing pattern within such interaction and to interpret player performance, a recent study has applied network science to the analysis of rallying in other racquet sports such as badminton. However, little has been done in tennis given it contains more constraints like ball location and wider court space. Therefore, this study aimed to construct a tennis stroke network that considers the consecutive ball placement during long rallies and to identify the prominent court zone within the network.